Hydrodynamic and thermal characterization of an Atlantic Forest (Research, Society and Development, 2021)
Soil hydrodynamic and thermal characterization are indispensable to support research related to the analysis of soil-plant-atmosphere interaction processes. Therefore, the objective was to carry out the hydrodynamic and thermal characterization of a soil that makes up a fragment of the Atlantic Forest, located in the Dois Irmãos neighborhood, in Recife, Pernambuco, Brazil. For this purpose, laboratory tests of granulometry and infiltration tests using a soil column. To obtain the hydrodynamic parameters, the Beerkan Estimation of Soil Transfer (BEST) methodology was followed, while the thermal properties of the soil were obtained from models proposed by De Vries (1963). After laboratory tests, the soil under analysis was classified as sandy loam. It was found that BEST provided coherent values for the shape and normalization parameters of the soil water retention and hydraulic conductivity curves. Regarding the thermal properties of the soil, a significant variation was observed with the increase in humidity, making it evident that water in the soil plays a determining role in the dynamics of heat propagation. The values of the hydrodynamic and thermal properties of the soil, provided by the different methods employed, were within the range established in the literature